Assessing the impact of research on society, economy and culture in the Humanities and Social sciences: a case study on a UK university campus (RT. A Journal on Research Policy and Evaluation, 2015)
The  aim  of  this  paper  is  to  describe  the  impact  of  research  on  society,  economy  and culture in the Humanities and Social sciences. In the first part of the paper, we describe the principal characteristics  of  the  evaluation  of  research  impact  in  the  United  Kingdom  (UK),  with  a  special focus on the new national exercise of research evaluation: the ‘Research Excellence Framework’ (REF2014). In the second part of the paper we present a case study in a British university campus where good practices of impact evaluation have been recently introduced. The main results of this study show that impact evaluation of Social sciences and Humanities research is a today’s key challenge  for  the  academia,  especially  due  to the  difficulty  in  identifying  the  appropriate  indicators for research impact measurement. Finally, we present the main themes of the current debate about the evaluation of the impacts in different fields of research